Book Review: Recognising the survival of marginal lives nearby Bengal borderlands - Siraj, Nasrin (Studies of Transition States and Societies, 2024)
Land, Life, Emotional Landscapes at the Margins of Bangladesh by Eva Rozalia Holze, 2022, Amsterdam University Press.